Young Muslims and Islamophobia in Italy: What is at Stake? - Viviana Premazzi (Culture e Studi del Sociale)
The objective of the paper is to highlight the complexity of Islam in Italy, between first and second generations, the role played by the media in depicting Islam as the ultimate otherness, discussing whether the success of Islamic fundamentalism in the world has resulted in new forms of Islamophobia in the Italian society and if and how Islamic communities reacted to that and what are the risks for the second generations and the Muslim communities at large. Thanks to a varied and extensive desk literature review analysis and qualitative interviews carried out in Italy with key informants (representatives of mosques and Islamic centres, presidents and directors of Muslim organizations of first and second generation, academics and experts on Islam in Italy), the contribution will outline the complex relationship between media, immigration and Islamophobia and the debate around it considering a national security perspective and the importance of social inclusion to prevent radicalism and to foster counter-terrorism policies.